Comprehensive Characterization of CK1δ-Mediated Tau Phosphorylation in Alzheimer’s Disease - Roth, Aileen; Sander, Annabelle; Oswald, Marleen Silke; Gärtner, Fabian; Knippschild, Uwe; Bischof, Joachim (Frontiers in Molecular Biosciences, 2022)
A main pathological event in Alzheimer’s disease is the generation of neurofibrillary tangles originating from hyperphosphorylated and subsequently aggregated tau proteins. Previous reports demonstrated the critical involvement of members of the protein kinase family CK1 in the pathogenesis of Alzheimer’s disease by hyperphosphorylation of tau. However, precise mechanisms and effects of CK1-mediated tau phosphorylation are still not fully understood. In this study, we analyzed recombinant tau441 phosphorylated by CK1δ in vitro via mass spectrometry and identified ten potential phosphorylation sites, five of them are associated to Alzheimer’s disease. To confirm these results, in vitro kinase assays and two-dimensional phosphopeptide analyses were performed with tau441 phosphomutants confirming Alzheimer’s disease-associated residues Ser68/Thr71 and Ser289 as CK1δ-specific phosphorylation sites. Treatment of differentiated human neural progenitor cells with PF-670462 and Western blot analysis identified Ser214 as CK1δ-targeted phosphorylation site. The use of an in vitro tau aggregation assay demonstrated a possible role of CK1δ in tau aggregation. Results obtained in this study highlight the potential of CK1δ to be a promising target in the treatment of Alzheimer’s disease.